2011
DOI: 10.1128/aac.00312-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altering Aminoglycoside Structures on Bacterial Resistance Enzyme Activities

Abstract: Aminoglycoside-modifying enzymes (AMEs) constitute the most prevalent mechanism of resistance to aminoglycosides by bacteria. We show that aminoglycosides can be doubly modified by the sequential actions of AMEs, with the activity of the second AME in most cases unaffected, decreased, or completely abolished. We demonstrate that the bifunctional enzyme AAC(3)-Ib/AAC(6)-Ib can diacetylate gentamicin. Since single acetylation does not always inactivate the parent drugs completely, two modifications likely provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…The main biochemical factor proposed is substrate channelling (49). This hypothesis is supported by studies that have demonstrated double modification of aminoglycosides in vitro (2,18). If dual modification proves to be relevant in vivo, substrate channelling may improve the efficiency of this process and lead to improved antibiotic detoxification for the host bacterium.…”
mentioning
confidence: 50%
“…The main biochemical factor proposed is substrate channelling (49). This hypothesis is supported by studies that have demonstrated double modification of aminoglycosides in vitro (2,18). If dual modification proves to be relevant in vivo, substrate channelling may improve the efficiency of this process and lead to improved antibiotic detoxification for the host bacterium.…”
mentioning
confidence: 50%
“…AG resistance results, in great part, from the evolution or acquisition of AG-modifying enzymes (AMEs) that acetylate (AG acetyltransferases [AACs]), phosphorylate (AG phosphotransferases [APHs]), or nucleotidylate (AG nucleotidyltransferases [ANTs]) various positions on the AG scaffolds, resulting in their deactivation as antibacterials (35). To broaden their AG resistance profile, bacteria have also evolved bifunctional AMEs, including AAC(6=)-30/ AAC(6=)-Ib (46), AAC(6=)-Ie/APH(2Љ)-Ia (2, 6), AAC(3)-Ib/ AAC(6=)-Ib= (14,19,25), and ANT(3Љ)-Ii/AAC(6=)-IId (9,24).…”
mentioning
confidence: 99%
“…Letter to modification by AMEs, 7 while in other cases acylation at this position is deleterious to antibacterial activity. Those results indicated that acylation can be a good methodology to generate novel active AG variants.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…The chemical modifications of AGs by AMEs, including AG Nacetyltransferase (AACs), AG O-phosphotransferases (APHs), or AG O-nucleotidyltransferase (ANTs), lead to a decreased affinity of the modified AGs for the ribosome. While we have shown that a single chemical modification does not necessarily remove all antibacterial activity, 7,8 the existence of bifunctional AMEs, such as AAC(3)-Ib/AAC(6′)-Ib′ 9 and AAC(6′)-30/ AAC(6′)-Ib′ 10 from Pseudomonas aeruginosa, AAC(6′)-Ie/ APH(2″)-Ia from Staphylococcus aureus, 11 and ANT(3″)-Ii/ AAC(6′)-IId from Serratia marcescens, 12 capable of performing two chemical modifications on AG scaffolds, and that of the enhanced intracellular survival (Eis) 13,14 enzyme capable of multiple acetylations increase the need for new AGs capable of evading the action of AMEs. Two main strategies for circumventing the activity of AMEs on AGs consist of (1) developing inhibitors of AMEs to be used in conjunction with currently approved AGs, and (2) making small modifications on the scaffolds of known AGs to yield products that remain active against bacteria, but are no longer modified by AMEs.…”
mentioning
confidence: 99%